Assessing groundwater suitability for irrigation: A case study for Durgapur upazila of Bangladesh - Das, Nilima; Rahman, Mohammed Mizanur; Islam, Md Touhidul; Adham, A K M (Fundamental and Applied Agriculture, 2019)
A study was carried out to evaluate the quality of groundwater and its suitability for irrigation in Durgapur upazila under Netrokona district of Bangladesh. Fifteen groundwater samples were collected from different tube- wells and analyzed for pH, electrical conductivity (EC), total dissolved solids (TDS), major cations like Ca2+, Mg2+, Na+, K+ and anions like Cl–, SO2–, PO3–, CO2–, HCO –. Based on these analyses, irrigation water quality parameters like sodium adsorption ratio (SAR), soluble sodium percentage (SSP), residual sodium carbonate (RSC), magnesium adsorption ratio (MAR), total hardness (TH), Kelly’s ratio (KR), permeability index (PI), potential salinity (PS) and salinity and alkalinity hazard were calculated. ArcGIS software was used to show the spatial distribution of different quality parameters across the study area. The groundwater of the study area was mildly acidic. Acidic water was observed in the north-eastern part of the study area. All the groundwater samples were found to be suitable for the irrigation in terms of EC, TDS, SAR, SSP, RSC, TH, KR, PI and PS, and whereas in terms of MAR, 5 samples were in ‘dangerous’ category. High MAR values of groundwater were observed in the north western part of the study area. However, in terms of salinity and alkalinity hazard, all of the water samples were categorized as ‘good to excellent’ class for irrigation. Piper diagram showed that Ca2+–Cl– type water was the dominant form of groundwater in the study area. Gibbs diagram indicated that most of the cations and anions had a precipitation dominance origin. Overall for the groundwater samples, PI-PS and SSP–KR had a very strong correlation with a correlation coefficient around 1, and whereas, Ca2+, Mg2+, K+ and MAR showed a negative correlation with most of the variables. The study revealed that the quality of the groundwater of the study area is suitable for irrigation.